Analisis Persediaan Drill Pipe dengan Pendekatan Economic Order Quantity (EOQ) pada Warehouse PT. XYZ - Syapolly, Dhea Ananda Novithalia Ardhany; Andrianti, Irma; Parji, Parji (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Inventory is goods reserved for a specific purpose. PT.XYZ certainly holds supplies of the materials they have. This research aims to calculate the economic order quantity, optimal order frequency, safety stock, and reorder point of existing drill pipe inventory at PT.XYZ using the Economic Order Quantity (EOQ) method. The results of this research are that companies should place orders for 3 ½